2017
DOI: 10.4314/ahs.v17i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of pre-lacteal feeding practices in urban and rural Nigeria; a population-based cross-sectional study using the 2013 Nigeria demographic and health survey data

Abstract: BackgroundPrelacteal feeding (PLF) is a barrier to exclusive breast feeding.ObjectiveTo determine factors associated with PLF in rural and urban Nigeria.MethodsWe utilized data from the 2013 Nigerian Demographic and Health Survey. Bivariate and multivariate analyses were used to test for association between PLF and related factors.ResultsPrevalence of PLF in urban Nigeria was 49.8%, while in rural Nigeria it was 66.4%. Sugar or glucose water was given more in urban Nigeria (9.7% vs 2.9%), plain water was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
(28 reference statements)
6
27
2
5
Order By: Relevance
“…Living in an rural residence is 53% times more likely feed prelacteal foods than urban residences in Ethiopia. This is in line with the study done in Nigeria [ 54 , 55 ]. This might be due to rural residences are relatively having low awareness about the risk of prelacteal feeding and also cultural practices are more common in rural communities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Living in an rural residence is 53% times more likely feed prelacteal foods than urban residences in Ethiopia. This is in line with the study done in Nigeria [ 54 , 55 ]. This might be due to rural residences are relatively having low awareness about the risk of prelacteal feeding and also cultural practices are more common in rural communities.…”
Section: Discussionsupporting
confidence: 92%
“…Women who gave birth at their home is 3.93 times more likely to practice prelacteal feeding than who gave birth at health institutions. This finding is consistent with the study done in Sub-Saharan Africa [ 15 ], Nigeria trained study [ 54 ] , Nigeria population based demographic and health survey [ 55 ], in Burkina Faso and South Africa [ 53 ]. This may be due to the fact that home delivery is attended by traditional birth attendants who do not have the knowledge of exclusive breastfeeding and the harms of prelacteal feeding practice.…”
Section: Discussionsupporting
confidence: 92%
“…PLF has, also, been associated with a fourfold increased risk in infant deaths from infectious diseases [10]. Several studies have found that socio-economic conditions, lack of knowledge and cultural beliefs may contribute to PLF [1113]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, the prevalence of pre-lacteal feeding (20.2%) was lower as compared to Ethiopian studies at Afar (42.9%) [ 20 ] and Harari regions (45.4%) [ 21 ], and this variation might be due to differences in study period, setting and sample size. Moreover, the prevalence was lower than studies in India (88%) [ 10 ], Vietnam (73.3%) [ 11 ], Nigeria (60.5%) [ 14 ], western Uganda (31.3%) [ 13 ] and Egypt (58%) [ 15 ], and the variation may be attributed to sample size and cultural differences among the study populations of the respective studies. The prevalence of prelactal feeding in the current study also revealed about 5 % decline in less than 5 years compared to the EDHS report of 2016 (26.5%) [ 17 ].…”
Section: Discussionmentioning
confidence: 65%